Developing a biomimicry framework for product development in textile research - Mondejar, Maria Janel V.
Biomimicry is a relatively new scientific field where biological templates are emulated to discover innovations and solve problems sustainably (Benyus, 2014). Being an approach to sustainability and innovation, biomimicry is continually gaining extensive applications in different fields. However, biomimicry appears to be an unexplored concept in Philippine textile research. The purpose of this study is to develop a biomimicry framework for product development in textile research such that more researchers and designers in the Philippines would be encouraged to apply this concept in innovating and solving problems sustainably. The study discussed and analyzed existing biomimicry researches, products, and projects from other countries. The study also identified textile researches with biomimicry application and used descriptive analysis in developing the said framework. Purposive sampling was applied in selecting the institutions where textile researches were screened in different levels and discussed. The researcher found that there are only three textile researches which actually applied biomimicry. These three researches were then analyzed against the taxonomies specified by Janine Benyus (2014) and Maibritt Pedersen Zari (2007). In this study, the researcher constructed a biomimicry framework for product development in textile research using the taxonomies specified by Benyus (2014) and Zari (2007) and the analysis done on the identified researches here and abroad. The researcher also found that biomimicry is not yet being intentionally applied in Philippine textile research so to promote the application of biomimicry in textile research, the researcher recommends the exposure of this concept as well as the constructed framework to students and institutions that conduct textile research.